Treatment of Nonclassic 11-Hydroxylase Deficiency with Ashwagandha Root - Daniel Powell; Taiga Inoue; Gül Bahtiyar; Gabriel Fenteany; Alan Sacerdote (Case Reports in Endocrinology)
An elderly woman presented with acne and male pattern alopecia, which upon diagnostic evaluation was found to be due to nonclassic 11-hydroxylase deficiency. We previously reported that Ashwagandha root ameliorates nonclassic 3-β-ol dehydrogenase and aldosterone synthase deficiencies. This is the first report of its use being associated with amelioration of nonclassic 11-hydroxylase deficiency, where its apparent effects appear to be dose-related.